Penyisihan Bahan Organik Alami pada Desalinasi Air Rawa Asin Menggunakan Proses Koagulasi-Pervaporasi - Aulia Rahma; Muthia Elma; Mahmud Mahmud; Chairul Irawan; Amalia Enggar Pratiwi; Erdina Lulu Atika Rampun (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
The high number of natural organic matter contain in wetland water may cause its water has brown color and not consumable. In other hand, intrusion of sea water through wetland aquifer create water become saline, notably on hot season. Coagulation is effective method to applied for removing of natural organic matter. However, it could not be used for salinity removal. Hence combination of coagulation and pervaporation process is attractive method to removing both of natural organic matter and conductivity of wetland saline water. The objective of this works is to investigate optimum coagulant doses for removing organic matter by coagulation process as pretreatment and to analysis performance of coagulation-pervaporation silica-pectin membrane for removing of organic matter and conductivity of wetland saline water. Coagulation process in this work carried out under varied aluminum sulfate dose 10-60 mg.L-1. Silica-pectin membrane was used for pervaporation process at feed temperature 25 °C (room temperature). Optimum condition of pretreatment coagulation set as alum dose at 30 mg.L-1 with maximum removal efficiency 81,8 % (UV254) and 40 % (conductivity). In other hand, combining of coagulation-pervaporation silica-pectin membrane shows both of UV254 and salt rejection extremely good instead without pretreatment coagulation of 86,8 % and 99,9 % for UV254 and salt rejection respectively. Moreover, water flux of silica-pectin membrane pervaporation with coagulation pretreatment shown higher 17,7 % over water flux of wetland saline water without pretreatment coagulation. Combining of coagulation and pervaporation silica-pectin membrane is effective to removing both of organic matter and salinity of wetland saline water at room temperature.